2005
DOI: 10.1002/pc.20131
|View full text |Cite
|
Sign up to set email alerts
|

Experimental modeling of the cure behavior of a formulated blend of DGEBA epoxy and C12-C14 glycidyl ether as a reactive diluent

Abstract: Microwave curing of polymer matrix composites has been suggested as an attractive substitute for conventional thermal curing. Formulations of epoxy and reactive diluents have the advantage of better wettability and uniform fiber impregnation. However, higher peak exotherms in large masses, and thus thermal overshoot, presents a challenge for cure cycle optimization. Therefore, building a reliable curing model will not only predict the behavior of these materials during actual processing, but also facilitate nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…During the past decade, a number of diagnostic techniques have been developed to evaluate the crosslinking degree of epoxy resins, including infrared spectroscopy, 14 differential scanning calorimetry, 15 and viscosity. 17 All of these techniques not only require well-equipped laboratory conditions and the destruction of the samples used but also are usually complex and costly to implement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, a number of diagnostic techniques have been developed to evaluate the crosslinking degree of epoxy resins, including infrared spectroscopy, 14 differential scanning calorimetry, 15 and viscosity. 17 All of these techniques not only require well-equipped laboratory conditions and the destruction of the samples used but also are usually complex and costly to implement.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the electrical industry, the requirements of the properties of VPI resins has become higher and higher, and much effort has been devoted to the modification of the mechanical, thermal, and electrical properties of epoxy resin. [5][6][7][8][9][10][11][12][13][14][15] One new type of VPI resin, which contains in situ sequential interpenetrating polymer networks (sIPNs) resulting from the curing of cycloaliphatic epoxy resin (CER) and trimethacrylate monomer [trimethylol-1,1,1-propane trimethacrylate (TMPTMA)], with more excellent properties than conventional VPI resins was developed in our previous study. 16 The macroscopic properties of polymeric materials are strongly dependent on their microstructures, which can lead the crosslinking structure of an epoxy resin to influence its physical, chemical, thermal, electrical, and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…This value was in agreement with that obtained from the t gel measurements (as is described later) and also with other bifunctional epoxy resin systems. Wisanrakkit and Gillham26 determined an E a value of 63.5 kJ/mol for systems based on diglycidyl ether of bisphenol A (DGEBA) and bifunctional amines; when DGEBA was used with diethylenetriamine, values between 56 and 59 kJ/mol were found 18, 27–30. Previously, Kissinger31 determined an E a value of 51.8 kJ/mol for the same reaction.…”
Section: Resultsmentioning
confidence: 93%
“…[22][23][24] The commercially available GE are generally multifunctional chemicals containing optional numbers of epoxy rings attached by different length of ether linkages. Leon et al,25 reported that the epoxy ring of GE initial reacts with amine.…”
Section: Introductionmentioning
confidence: 99%
“…Glycidyl ether (GE) is a widely known reactive diluent and has been used in many applications, especially in epoxy adhesives 22–24. The commercially available GE are generally multifunctional chemicals containing optional numbers of epoxy rings attached by different length of ether linkages.…”
Section: Introductionmentioning
confidence: 99%